Konstipasi pada Kehamilan - Ligat Pribadi Sembiring (Fakultas Kedokteran Universitas Riau, 2015)
Constipation is a condition often found in pregnant women and can lead to various complications. Based onpathophysiology, constipation can be classified into constipation due to structural abnormalities and functionalconstipation. Constipation in pregnant women is classified as the functional constipation caused by hormonal factors,changes in diet, growth of fetus, decrease in physical activities and the position of the defecation. The management ofconstipation during pregnancy take precedence on non pharmacological therapy. Pharmacological therapy (laxatives)that can be used is the bulk-forming agents and osmotic laxatives, however, they are only when absolutely necessaryand are not for long term use. The reasons are to avoid dehydration and electrolyte imbalance in pregnant women.